(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Doris Lessing’s short stories “Little Tembi” and “No Sale for Witchcraft” are profound explorations of cultural identity, racial prejudice, and social conflict, rendered through rich symbolic imagery. This article employs close textual analysis and theoretical frameworks from literary criticism to investigate the symbolic devices Lessing employs to deepen her narratives. In “Little Tembi,” the protagonist’s journey symbolizes the tensions between tradition and modernity, personal freedom, and cultural displacement. Conversely, “No Sale for Witchcraft” uses witchcraft symbolism to critique racial stereotypes and societal fear of the unfamiliar. The study reveals how these symbolic images invite readers to reflect on postcolonial realities, social injustice, and the resilience of marginalized communities. Ultimately, the findings highlight Lessing’s skillful use of symbolism as a tool for social critique and empathy, underscoring her lasting significance in literary and cultural discourse.